FILSAFAT PENDIDIKAN PESANTREN DI INDONESIA: STUDI MELALUI NOVEL KEMBARA RINDU KARYA HABIBURRAHMAN EL SHIRAZY - Yusuf Aliputro; Anas Ahmadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study uses an educational philosophy approach to examine the philosophy of Islamic boarding school education in Habiburrahman El Shirazy's novel Kembara Rindu. The values of Islamic boarding school education, which are focused not only on imparting Islamic knowledge but also on helping students develop their morality, spirituality, and character, are embodied in the novel Kembara Rindu. In order to discover educational values based on an axiological perspective and their link to the disciplines of educational philosophy (ontology, epistemology, and axiology), this study employs a qualitative approach with a content analysis method on the novel text. Reduction methods, classification, and philosophical meaning interpretation are used to study data. The study's findings demonstrate that the novel "Kembara"'s Islamic boarding school education philosophy places a strong emphasis on the virtues of monotheism, sincerity, patience, manners, responsibility, and independence as the cornerstones for creating the ideal human being. The interaction between the students and the kiai (Islamic scholars), the tradition of knowledge, the practice of riyaḍah (religious devotion), and the social dynamics of the Islamic boarding school all reflect these ideals. The study's findings demonstrate that the novel "Kembara"'s Islamic boarding school education philosophy places a strong emphasis on the virtues of monotheism, sincerity, patience, manners, responsibility, and independence as the cornerstones for creating the ideal human being. The interaction between the students and the kiai (Islamic scholars), the tradition of knowledge, the practice of riyaḍah (religious devotion), and the social dynamics of the Islamic boarding school all reflect these ideals.